Palladium-Catalyzed ortho-Alkylation of Iodoarenes Enabled by a Cooperative Cycloolefin Ligand and a Bulky Trialkylphosphine - Wang, Xiao-Xia; Jiao, Lei (Synlett, 2025)
We recently achieved ortho-alkylation of iodoarenes utilizing a dual-ligand catalytic system that effectively combines palladium/olefin ligand cooperative catalysis with reversible C(sp2)–I reductive elimination enabled by a bulky trialkylphosphine ligand. Through careful mechanistic investigations, we confirmed the compatibility of the crucial steps involved in this process by isolating key organometallic intermediates and studying the stoichiometry of their transformations. By utilizing this protocol, we successfully achieved the ortho-alkylation of a variety of iodoarene substrates, thereby expanding the scope of applications for Catellani-type reactions. This study showcases the synthetic potential of the Pd/olefin ligand cooperative system as an innovative complement to established Pd/norbornene catalysis. In this Synpacts article, we present the conceptual framework underpinning this reaction and detail the key aspects of its development.1 Introduction2 Research Background2.1 The Catellani Reaction: Pd/Norbornene Catalysis2.2 Cooperative Cycloolefin Ligands for the Catellani-Type Reactions2.3 C–X Reductive Elimination on Pd Center3 Development of the Reaction3.1 Proof-of-Concept by Stoichiometric Reactions3.2 Substrate Scope and Synthetic Applications4 Conclusion
Keywords: ortho-alkylation; iodoarene; reductive elimination; cooperative olefin ligand; palladium catalysis; Catellani reaction